2003
DOI: 10.1002/ajmg.a.20134
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway malformation associated with partial trisomy 11q

Abstract: 11q trisomy is associated with a recognizable pattern of multiple malformations. Review of the literature reveals the following recurrent themes common to complex and isolated 11q trisomy: mental retardation, pre- and postnatal growth retardation, hypotonia, a distinct pattern of facial features, congenital heart defects, and limb malformations. We report four patients with partial trisomy 11q, none of which arose from the common 11/22 translocation. Three of the four patients had the previously unreported fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 24 publications
3
43
1
Order By: Relevance
“…Phenotypic features include growth and mental retardation, hypotonia and congenital heart defects, some of which features were observed in case 20. It has been proposed that the region 11q21-23.2 may be associated with certain upper airway malformations (Zhao et al, 2003). Inheritance status is unknown at the time of writing.…”
Section: Abnormal Postnatal Karyotype Following Normal Prenatal Qf-pcmentioning
confidence: 99%
“…Phenotypic features include growth and mental retardation, hypotonia and congenital heart defects, some of which features were observed in case 20. It has been proposed that the region 11q21-23.2 may be associated with certain upper airway malformations (Zhao et al, 2003). Inheritance status is unknown at the time of writing.…”
Section: Abnormal Postnatal Karyotype Following Normal Prenatal Qf-pcmentioning
confidence: 99%
“…This suggests that the altered cry in der(5)t(5p;11q) individuals may be independent of 11q gene dosage and is directly related to partial 5p deletion. The cry in der(5)t(5p;11q) infants has been described as either catlike (Mann and Rafferty, 1972;Mutchinick et al, 1988), high-pitched (Zhao et al, 2003), or was presumed normal (Wallerstein et al, 1992), and such phenotypic variability reflects that reported in the literature for the cry in Cri du chat syndrome (CDCS). These findings support the possi- Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Of all segmental trisomy 11q cases described to date, including those with 'pure' partial trisomy 11q (Pfeiffer and Schutz, 1993;de Die-Smulders and Engelen, 1996;Legius et al, 1996;Smeets et al, 1997;Delobel et al, 1998;Zhao et al, 2003;Yelavarthi and Zunich, 2004), only those involving translocation of the 11q segment to 5p are associated with an abnormal cry. This suggests that the altered cry in der(5)t(5p;11q) individuals may be independent of 11q gene dosage and is directly related to partial 5p deletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations